Clinical and epidemiological profile of the patients with anterior cruciate ligament tear attending a tertiary care hospital at Srinagar - Gilani, Mohamad Azhar; Mir, Naseer Ahmad; Lone, Aadil Hussain (International Journal of Research in Orthopaedics, 2023)
Background: Anterior cruciate ligament (ACL) is the most frequently injured knee ligament especially as regards sports that include movements with sudden direction changes as knee supports body weight during them. The ACL is crucial in stabilizing the knee joint. The objective of the study was to describe the general and clinical profile of the patients having ACL tear. Methods: This was a hospital based cross-sectional observational study. It was conducted on patients with ACL tear presenting to the department of orthopaedics SKIMS medical college and hospital Bemina from-December 2019 to June 2021. Information was obtained about the general characteristics and clinical profile of the patients. Knee stability was assessed by stability tests, Lysholm knee scoring and international knee documentation committee (IKDC) scale. Results: Of the 40 patients, 50% belonged to the age-group of 31-50 years, 90% were males and 57.5% (n=23) were from rural areas. Sports injury was most common 35%. Giving way was the most common presenting symptom (100%) followed by locking (57.5%). Maximum patients 25(62.5%) had a score of 2 for manual Lachman grading, anterior drawer test 28 (70%) and Pivot shift grading 21(52.5%) whereas for Tegner activity level 23 (57.5%) had a score of 3. The mean Lysholm knee scoring was 64.65±6.82 and the mean IKDC scoring was 51.88±6.70. Conclusions: ACL injury is mostly found in young people with active lifestyle. Sports related activities and road traffic accidents are the most common cause of ACL injury. Giving way and locking of the knee are the most common symptoms.